2019
DOI: 10.3928/01484834-20190521-02
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Bounce Back: A Scoping Review About Resiliency Education

Abstract: Background: Health care professionals face high levels of stress from working in a demanding environment. Resiliency training has emerged as an approach to overcome occupational stress. The purpose of this study was to understand what is known about educational strategies for teaching resilience. Method: The five-stage approach from Arksey and O'Malley was used as the methodological framework. Resources were evaluated thematically to identify key strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…The third theme, "building on strengths," is an essential component of resilience training and a welcome change to athletes who described lifelong efforts focused on improving their weaknesses. These results are consistent with previous research that associated strengths-based dialogue with increases in student self-efficacy, persistence, role engagement, and connections with the institutional community (Low, King, & Foster-Boucher, 2019;Soria & Stubblefield, 2015). A sense of belonging, or relatedness, was fostered by writing.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The third theme, "building on strengths," is an essential component of resilience training and a welcome change to athletes who described lifelong efforts focused on improving their weaknesses. These results are consistent with previous research that associated strengths-based dialogue with increases in student self-efficacy, persistence, role engagement, and connections with the institutional community (Low, King, & Foster-Boucher, 2019;Soria & Stubblefield, 2015). A sense of belonging, or relatedness, was fostered by writing.…”
Section: Discussionsupporting
confidence: 91%
“…These preliminary results are similar to those of a study that focused on firstgeneration, underresourced students that suggested a supportive, culturally attuned campus environment may increase healthy student adaptation, belonging, and success (Museus, Yi, & Saelua, 2017). Interestingly, a recent review of resilience courses for nurses recommends including components of training similar to the current intervention: reflection, storytelling, peer mentoring, mindfulness, social support, and enhancing self-knowledge and personal competencies (Low et al, 2019).…”
Section: Implications For College Healthsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, training programs and improvement of individual well-being can help develop psychological capital. 9,10,[12][13][14][15][16][17] External promoting factors are found in workplace and practice environments. Evidence from the literature positively correlates autonomy in practice, strong nursing leadership, empowerment, supportive social networks, availability of resources, and encouragement of self-care with healthy, resilient work and practice environments.…”
Section: Background and Rationalementioning
confidence: 99%
“…The critical need for resiliency training and education is very relevant for healthcare professionals today. 14 Education tailored to defining the process of resilience-building with evidence-based techniques, exploring the attributes and behaviors of resilient individuals and teams, and discussing the relevance of resilience will serve as a useful approach in developing healthy workforces. 9 Implementing resilience education will help nurses identify stressors, encourage participation in self-care techniques, and foster emotional intelligence.…”
Section: Educationmentioning
confidence: 99%